Chloroquine Attenuates Asthma Development by Restoring Airway Smooth Muscle Cell Phenotype Via the ROS-AKT Pathway - Ren, Yan; Zhong, Xiuhua; Wang, Hongyu; Chen, Zhongqi; Liu, Yanan; Zeng, Xiaoning; Ma, Yuan (Frontiers in Pharmacology, 2022)
Switching of airway smooth muscle (ASM) cell phenotype from differentiated-contractile to dedifferentiated-proliferative/synthetic state often occurs in asthmatic subjects with airway dysfunction. Evidence has been provided that chloroquine (an agonist of bitter taste receptors) presented benefits to ASM cell function implicated in asthma. However, the underlying mechanism is unclear. House dust mite (HDM)-sensitized mice were administered with chloroquine or dexamethasone before challenge. BALF and lung tissue were obtained for cell counting, histological analysis or ELISA. Primary cultured ASM cells were stimulated with transforming growth factor (TGF)-β1 or H2O2. Cells and supernatant were collected for the detection of ASM phenotype, ROS level, and proinflammatory cytokine production. In HDM-sensitized mice, chloroquine attenuated airway hyperresponsiveness (AHR), inflammation and remodeling with an inhibition of immunoglobulin E, IL-4/-13 and TGF-β1 in BALF. ASM cell proliferation (PCNA), hypertrophy (α-SMA), and parasecretion (MMP-9 and MMP-13) were strongly suppressed by chloroquine, hinting the rebalance of the heterogeneous ASM populations in asthmatic airway. Our data in vitro indicated that chloroquine markedly restrained maladaptive alteration in ASM phenotype in concert with a remission of ROS. Using H2O2 and PI3K inhibitor (LY294002), we found that the inhibition of oxidative stress level and ROS-AKT signal by chloroquine may serve as a potential mechanism that dedicates to the restoration of the phenotypic imbalance in ASM cells. Overall, the present findings suggested that chloroquine improves asthmatic airway function by controlling ASM cell phenotype shift, sketching a novel proﬁle of chloroquine as a new therapeutic candidate for airway remodeling.